ATTUNING STUDENTS’ ATTENTION THROUGHOUT A LECTURE - S.ROOPA (International Journal of Pharma and Bio Sciences, 2014)
The lectures in most of the dental colleges are of one hour duration. The concentration of the students is lost quickly and the attention level of the students is hard to maintain. This study was conducted to find out the opinion of students whether the ‘lecture with interactive intervals’ helps to keep the concentration levels high throughout the lecture, refocus the attention back and learn better. The study was done on dental students (n=86). Few interactive sessions were incorporated in a one hour lecture. Students’ feedbacks were obtained using a structured questionnaire consisting of three questions on a 3 point Likert scale. Statistical analysis was done using SPSS software-15 version. The percentage of students who agree is more than the percentage of students who have no opinion and who disagree on all the three criteria. Students’ attention can be refocused and their concentration levels kept high by ‘lecture with interactive intervals’.